Conceptualisation of nation brand image - Handayani, Bintang; Rashid, Basri (Universiti Utara Malaysia, 2013)
This paper examines the nation brand image notion. Literature review is employed as the method to develop the conceptual model.This paper suggests that the multifaceted nature of a nation can be covered in the nation brand image.In addition, the theoretical relationship between national brand identity, national identity, tourism brand and nation brand image and is also explored.This paper eventually proposes a conceptual model of nation brand image and suggests that future research include the multi elements of national brand identity and national identity as the components of nation brand image.